Evaluasi Kebijakan Publik dalam Mitigasi Krisis Sosial Banjir Tahunan: Studi Kasus Kabupaten Kutai Barat Tahun 2024 - Dina Fadiyah; Agustinus (Journal of Politics and Democracy, 2026)
This study aims to evaluate the effectiveness of public policy in mitigating the social crisis caused by annual flooding in West Kutai Regency in 2024. The study employs a qualitative approach using a case study design. Data were collected through in-depth interviews, observation, and document analysis involving local government officials, community leaders, and affected residents. The data were analyzed using a descriptive-interpretative approach to examine the gap between policy design and its implementation. The findings indicate that policy effectiveness remains suboptimal. Although the initial emergency response was relatively rapid, the policy failed to fulfill key dimensions of effectiveness, responsiveness, and adequacy. The main issues include weak inter-agency coordination, inappropriate physical programs that neglect local knowledge, low transparency in aid distribution, and limited attention to the social and psychological dimensions of affected communities. Furthermore, community participation in policy planning remains largely symbolic, resulting in policies that are less contextual and less responsive to local needs. This study highlights that disaster mitigation challenges are not merely technical issues but also reflect weaknesses in governance, particularly in integrating institutional, social, and participatory dimensions. Therefore, improving policy effectiveness requires a more integrated, participatory, and long-term recovery-oriented approach to reduce social vulnerability in disaster-prone areas.